Here's the question you clicked on:
gfields444
What are the zeros of the polynomial function: f(x) = x^3 – 5x^2 + 6x
first take out x: f(x) = x(x^2 - 5x + 6) = 0 (x(x - 3)(x - 2) = 0 can you continue?
i still do no understand
did you understand why i took the x out?
0, –3, 2 0, 3, –2 0, –3, –2 0, 3, 2 I got these four answers
do you understand why there's three answers?
yes but i dont know which one is correct, i tried four different times and ended up with these ugh
The zeroes is just where y = 0. So pretend f(x) is your y and plug in 0. 0 = x^3 – 5x^2 + 6x Do you know how to solve this? Just ignore f(x)
I would start by factoring first, all of these numbers have a common factor, x. x (x^2 - 5x + 6) Now, factor it further by factoring x^2-5x+6 You get (x-3)(x-2) you're left with x(x-3)(x-2) Equal each of these expressions to zero. x=0 x - 3 = 0, which is x=3 x - 2 = 0, which is x =2